Neurophysiological Correlates of User Experience in Smart Home Systems (SHSs): First Evidence From Electroencephalography and Autonomic Measures - Angioletti, Laura; Cassioli, Federico; Balconi, Michela (Frontiers in Psychology, 2020)
Home automation brings together technology, engineering and user experience (UX). Neuroscience could be a valuable discipline to explore UX. For the first time, in the present work, some distinguishing effects of domotics on users’ cognitive and emotional behavior are highlighted by using the neuroscientific approach. To define possible effects of Smart Home System (SHS) on UX, a neuroscientific multi-methodology was adopted for recording and confronting the neural activity (Electroencephalography, EEG) and autonomic system responses of 19 individuals during a resting state (RS) baseline and the exploration of 5 different tech-interaction areas in a domotic environment. EEG findings showed a generalized neural activation reflected by alpha band activity while participants were exploring the tech-areas confronted with the RS. Delta band was mainly present in temporo-central compared to frontal and parieto-occipital areas and was interpreted as a higher emotional activation related to the whole UX. This effect was found for the sixth tech-interaction area (i.e. bedroom) compared to the RS, and it is supposed to represent an enhanced emotional response and integration processing towards a higher multisensory interactive area. Regarding autonomic activity, an increase in heart rate was found for the bedroom area compared to the RS, thus showing a specific effect on physiological indices in this engaging tech-area. The present research constitutes the first attempt to understand the user responsiveness to SHS, in terms of cognitive and emotional engagement, by adopting a neuroscientific perspective. Some high-value benefits derived from this approach will be described at the light of neurophysiological results.